Archaism in Shamloo’s Poetry - ahmad khatami (Matn/Pizhūhī-i Adabī, 2012)
Language is an important element of poetry. In Russian formalism and structuralism, investigating into language is of great significance. The basis of these schools is mostly related to the prominence of literary texts and their distance from ordinary language use. An important way to make literary texts distinguished from others is violation of norms, among which archaism can be used to create beauty in a literary work. If a poet or writer takes an archaic approach in his/her language, his/her work is called archaic. Ahmad Shamloo is among the contemporary poets who has used archaism as the basis of his poetry. He pays attention to old texts as a great linguistic source for making his poetry outstanding. This paper aims at investigating into the archaic aspects of Shamloo poems using formalism and structuralism.